Bimbingan Agama Islam Dalam Meningkatkan Ketenangan Jiwa Warga Binaan Wanita Di Lapas Kelas II A Banyuwangi - Alfira, Rizka; Yohandi; Suliaman, A. Husam (Jurnal Ilmu Bimbingan dan Konseling, 2025)
This study aims to determine the role of Islamic religious guidance in improving the mental serenity of inmates in cases of embezzlement and motorycycle fraud at Class IIA Banyuwangi Prison. The research method used is qualitative with a descriptive approach. The results showed that Islamic religious guidance can help improve the mental serenity of inmates by providing an understanding of religious and moral values. Islamic religious guidance can also help inmates to overcrome stress and anxiety experienced during the period of punishment. In addition, Islamic religious guidance can also help inmates to increase self awareness and responsibility for their actions. This study also found that Islamic religious guidance can help inmates to improve their quality of life and prepare themselves for reintegration into society. This research is expected to contribute to the development of Islamic religious guidance in correctional institutions and improve the quality of life of inmates.